Li-ion storage in orthorhombic hydrated sodium molybdate with oxygen-vacancy defects - Nguyen, Tuan Loi; Vo, Thuan Ngoc; Phung, Viet Duc; Ayalew, Kaleab; Chun, Dongwon; Luu, Anh Tuyen; Nguyen, Quang Hung; Kim, Kwang J.; Kim, Il Tae; Moon, Jaeyun (ELSEVIER SCIENCE SA, 2022)
Two orthorhombic salts (OHMs) of Na2MoO4.(H2O)(2) were prepared at 130 C (OHMs_130) and 170 C (OHMs_170) via a hydrothermal process, followed by heat treatment. Advanced analyses proved the formation mechanism of the layered structures of unique OHMs. All OHMs possessed layered structures with many empty channels and numerous oxygen vacancies (VO). VO were formed due to the absence of O atoms in tetrahedra MoO4 (Vsh-O) and the loss of H2O molecules (Vwater-O) in the OHMs structure. Despite the micro-sizes of OHMs crystals, the OHMs-based anodes in Li-ion batteries exhibited superior cyclic and rate performance. OHMs_170 electrode exhibited higher capacity retention (91.6% after 200 cycles) and rate capability (80% at 3 A g-1) than OHMs_130. It is attributed to the advantageous formation of a higher amount of Vwater-O and a low amount of Vsh-O in the OHMs_170 leading to the stable structure of the electrodes and fast Li+ ion movements during charge/ discharge processes. In addition, the electrochemical impedance spectroscopy, Randles-Sevcik equation, and kinetic study results suggested that the exceptional performance of the OHMs_170 electrode came from low resistance, pseudo behavior, and fast Li+ mobility inside the OHMs structure.